Analysis of the robustness of energy supply in Japan: Role of renewable energy. (November 2020) - Zhu, Danmei; Mortazavi, Seyed Mostafa; Maleki, Akbar; Aslani, Alireza; Yousefi, Hossein
Abstract: Today, the security of energy has become one of the primary concerns of all the countries around the world due to the limited energy sources, increasing population, energy prices fluctuations and limitations in energy supply. Japan is considered as one of the largest energy consumers and energy importers throughout the world which almost 96% of its primary energy supply in national level relies on the imports from other countries. After experiencing several harsh energy supply conditions over the last 40 years, Japan realized the sensitivity of its energy supply and decided to fundamentally restructure its energy supply and rely more on energy mix diversification, renewable energies, energy efficiency improvement, and carbon emissions reduction. In this article the energy security improvement and the government actions to boost diversification of energy by focusing more on renewable energies and reducing energy intensity, increasing energy efficiency and decreasing energy import dependency in Japan is studied. In addition, various renewable energy technologies as a substitute source of energy and promising ways of domestic energy supply as well as the factors to improve the security of energy supply are studied thoroughly. Moreover, it was realized that the most primary energy sources in Japan are biofuel and waste energy followed by hydropower and geothermal energy respectively. Highlights: Various renewable energy resources in Japan are reviewed. Government policy instruments to promote renewable energy in Japan are discussed. The energy security and the sensitivity of energy supply in Japan are summarized. The role of energy diversification and carbon emissions reduction are described.